2016
DOI: 10.31018/jans.v8i2.874
|View full text |Cite
|
Sign up to set email alerts
|

Constraints faced by farmers of Haryana state in adoption of masumbi (Citrus sinensis) cultivation

Abstract: The study focused on the constraints faced by farmers of Haryana state in adoption of masumbi (Citrus sinensis) cultivation. The study was conducted in Bhiwani district. The constraints as perceived by the respondents were measured by the scores on the basis of magnitude of the problems. Constraints were categorized into inputs, marketing, production, technical and psychologicalconstraints. While analyzing overall constraints as perceived by farmers the findings revealed that high price of insecticides/pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…While on the other hand, the robots can change the culture (Z score= -1.69) was encountered as not so serious constraint. These fi ndings were found to partially support by reports of Kumar et al (2016). Constraints in using weather forecast : The Table 1 revealed that complex maintenance (Z score= 1.29) and availability of historical and real time data (Z score= 1.38) were very serious constraint, Whereas complex physical features (Z score= -0.76), cost distribution of the service (Z score= -0.76), capacity of forecasters to receive and use the available products (Z score= -0.38) and supporting policies and capacities of users to apply the information (Z score= 0.27) were serious constraints encountered in using weather forecast in agriculture.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While on the other hand, the robots can change the culture (Z score= -1.69) was encountered as not so serious constraint. These fi ndings were found to partially support by reports of Kumar et al (2016). Constraints in using weather forecast : The Table 1 revealed that complex maintenance (Z score= 1.29) and availability of historical and real time data (Z score= 1.38) were very serious constraint, Whereas complex physical features (Z score= -0.76), cost distribution of the service (Z score= -0.76), capacity of forecasters to receive and use the available products (Z score= -0.38) and supporting policies and capacities of users to apply the information (Z score= 0.27) were serious constraints encountered in using weather forecast in agriculture.…”
Section: Resultssupporting
confidence: 86%
“…The present study got support from the past research fi ndings of Kumar et al (2016) who reported that major constraints were higher prices, insuffi cient funds for small entrepreneurs, lack of skill and awareness, higher cost of machinery and poor support on marketing. Constraints related to policy : The Table 1 revealed that no supporting budget to buy equipment (Z score= 1.44) was very serious constraint, whereas government funds are not available (Z score= 0.00), no separate budget for the promotion of AI (Z score= 0.72), no subsidy available for AI tools (Z score= -0.36) and no separate government department for training (Z score= 0.60) were serious constraints related to policy in using artifi cial intelligence in agriculture.…”
Section: Methodssupporting
confidence: 79%
“…These constraints can be overcome by providing easy marketing facilities coupled with fixed minimum support price of farm produce. These research findings are confirmed from the findings of Sharma (2014), Kumar et al (2016) and Kumar et al (2018).While, Gunaseelan and Singh (2018) concluded that there is a need to establish market and effective marketing network.…”
Section: Constraints In Adoption Of Irrigation and Drainagesupporting
confidence: 71%
“…Fruit cultivation is a diversified agriculture activity significantly generating employment throughout the year enhances farm economy and also earns foreign exchange by enhancing export (Parkash 2000). Fruits are essential for human diet as main source of nutrition, indirect diversity, ecological sustainability and fight against hunger (Kumar et al 2016). Citrus is one of the most relevant fruit crops grown across the globe and has a tremendous social, cultural and economic influence on our society (Vijaya et al 2017).…”
mentioning
confidence: 99%